2022
DOI: 10.5194/egusphere-2022-451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hotspots and drivers of compound marine heatwave and low net primary production extremes

Abstract: Abstract. Extreme events can severely impact marine organisms and ecosystems. Of particular concern are multivariate compound events, namely when conditions are simultaneously extreme for multiple ocean ecosystem stressors. In 2013–2015 for example, an extensive marine heatwave (MHW), known as the Blob, co-occurred locally with extremely low net primary productivity (NPPX) and negatively impacted marine life in the northeast Pacific. Yet, little is known about the characteristics and drivers of such multivaria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…For example, Noh et al (2022) reported that MHWs typically reduce Chl in the tropical and subtropical regions, where background nitrate concentrations are insufficient. Le Grix et al (2021) discovered frequent compound MHW-LChl events in the central equatorial Pacific and Indian Ocean, which corresponds to the co-occurrence of MHWs and low net primary productivity events (Le Grix et al, 2022). However, the features of compound MHW-LChl events over the marginal seas are not revealed in Le Grix et al (2021), we perform a more detailed analysis of multi-scale characteristics of compound MHW-LChl extremes over the western Pacific Ocean, including the marginal seas regions.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…For example, Noh et al (2022) reported that MHWs typically reduce Chl in the tropical and subtropical regions, where background nitrate concentrations are insufficient. Le Grix et al (2021) discovered frequent compound MHW-LChl events in the central equatorial Pacific and Indian Ocean, which corresponds to the co-occurrence of MHWs and low net primary productivity events (Le Grix et al, 2022). However, the features of compound MHW-LChl events over the marginal seas are not revealed in Le Grix et al (2021), we perform a more detailed analysis of multi-scale characteristics of compound MHW-LChl extremes over the western Pacific Ocean, including the marginal seas regions.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…The study of the relationships between extreme events (e.g., compound events) is very recent (Gruber et al., 2021; Le Grix et al., 2022), and there are still many questions to be answered about their interactions and functioning at the physical level, in particular the quantification of the decrease in NPP associated with MHWs of different intensity and occurring at different locations. Thus, it seemed extremely ambitious to address this issue at the biological level, so we chose to free ourselves from this relationship and thus fixed net primary production in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, associated with MHWs, as under global warming, the abrupt increase in temperature causes an increase in surface water stratification and changes in nutrient availability. At low latitudes, MHWs could be associated with a decrease in nutrients at the ocean surface and, thus, a decrease in phytoplankton growth, leading to an extreme drop in primary production (Le Grix et al, 2022). These two extreme events could have an additional or synergic negative effect on the functioning and stability of marine ecosystems with cascading impacts through the food web depending on which types of phytoplankton marine species prefer to graze on (Bindoff et al, 2019;Cavole et al, 2016;Cheung & Frölicher, 2020).…”
Section: Primary Production and Mhw Relationmentioning
confidence: 99%
“…E. Smith et al, 2023). But also ocean acidity extremes (OAX) (Hauri et al, 2013;Kwiatkowski & Orr, 2018;Negrete-García et al, 2019;Burger et al, 2020;Desmet et al, 2022) and low oxygen extremes (LOX) (Chan et al, 2008;Hofmann et al, 2011;Köhn et al, 2022) are receiving increasing attention, with the study of compound marine extremes, that is, events when conditions are extreme in more than one stressor emerging as an -2-manuscript submitted to AGU Advances issue of special concern (Gruber et al, 2021;Le Grix et al, 2021;Burger et al, 2022;Le Grix et al, 2022). Such compounded extreme events can have a disproportionately large impact on marine biota, especially when the different stressors act synergistically, that is, when they reinforce each other (Crain et al, 2008;Boyd & Brown, 2015;Pirotta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%